(3GdGcJaG aj WdH GdTaGs - (3eLghds; (3GHf GdHjWGQs
(3ChdgG (B:s
(3GdMeO ddg Pj GdYXeI hGdcHQjGA GdefaQO HGdYRI hGdHbGA Ndb GdEfSGf ef SdGdI ef Wjf s
(3BNQgG (B:s
(3ef HGH GdNhGU(B: (3ReQO(B: (3ef JbdO MLQkG efg, Ch JNJe Hg OaY Yfg OGA GdUQY bGd(B: (3hef CLd Pdc UQfG fCeQ Gdedhc Cf JYdbg Ydi ChdGOgG YfO hdGOJge djOaY OGA GdUQY Yfge s
(3hgh GNJUGQ dcJGH GdLGeY aj GdCOhjI GdeaQOI dGHf GdHjWGQs
(3hbO QJHg Ydi YTQjf HGHkGs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B30 s
Keywords: (3GdWHs